1992
DOI: 10.1063/1.463698
|View full text |Cite
|
Sign up to set email alerts
|

Use of an improved ion–solvent potential-energy function to calculate the reaction rate and α-deuterium and microsolvation kinetic isotope effects for the gas-phase SN2 reaction of Cl−(H2O) with CH3Cl

Abstract: We present calculations of the rate constants and secondary kinetic isotope effects for the gas-phase SN2 reaction Cl−(H2O)+CH3Cl based on a new chloride–water potential-energy function that has been specifically converged for heavy-water isotope effects. The results are compared to new calculations employing five chloride–water potential-energy functions that have been developed for simulations of aqueous solutions. In all calculations the ClCH3Cl− solute intramolecular potential is taken from a previous semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 80 publications
5
52
1
Order By: Relevance
“…The PCM model has been shown to underestimate the trend in increase of activation energies relative to the gas phase, which depends on the dielectric constant of the solvent. Finally it should be noted that other studies of solvated S N 2 reactions have been reported, but their main focus has been on equilibrium and non-equilibrium solvent effects, and kinetic solvent isotope effects [34][35][36][37][38][39]. These topics, while interesting and important, will not be discussed, within the context of the present work.…”
Section: Introductionmentioning
confidence: 86%
“…The PCM model has been shown to underestimate the trend in increase of activation energies relative to the gas phase, which depends on the dielectric constant of the solvent. Finally it should be noted that other studies of solvated S N 2 reactions have been reported, but their main focus has been on equilibrium and non-equilibrium solvent effects, and kinetic solvent isotope effects [34][35][36][37][38][39]. These topics, while interesting and important, will not be discussed, within the context of the present work.…”
Section: Introductionmentioning
confidence: 86%
“…All have been studied computationally in different contexts, some involving tunneling . Tunneling has not been reported in R12 and R13, but Truhlar and co‐workers have studied tunneling in the gas phase S N 2 reactions Cl − (H 2 O)+ CH 3 Cl → ClCH 3 + Cl − (H 2 O), CH 3 NH 3 + Cl − → CH 3 Cl + NH 3 and CH 3 Cl(H 2 O) + NH 3 (H 2 O) → CH 3 NH 3 + Cl − (H 2 O) 2 …”
Section: Methodsmentioning
confidence: 99%
“…Refs. [2][3][4][5][6][7][8][9][10][11] This is because the underlying reaction dynamics could add to our understanding of how to apply our extensive knowledge of gas phase reactions to systems in the liquid phase. A recurrent finding for almost all of these reactions is that the formation of solvated reaction products is strongly suppressed with respect to their unsolvated counterparts.…”
Section: Introductionmentioning
confidence: 99%